These boots are made forwalking. (Economist, 2016)
The article reports that the Stockholm, Sweden-based music-streaming company Spotify has announced it may look to relocate its headquarters. Reasons cited for the move include the expense and availability of rental properties in the city, the cost of taxes on stock given to employees, and the lack of computer programming taught in Swedish schools.